Marketing communication strategy for Taransit application in India - Ivanov, Jakub (2024)
The thesis examines the development of a marketing communication strategy for Taransit, an application designed to simplify public transport navigation in India. Using qualitative interview, quantitative research, and secondary data analysis, the research examines how marketing strategies align with Taransit’s business objectives, identifies the main characteristics of the target audience, and evaluates the effectiveness of communication platforms. Main insights highlight that WhatsApp and YouTube are the most widely used communication platforms among Taransit’s user base, with engagement peaking during late evenings. These findings underpin the proposed communication plan, which prioritises these platforms to deliver targeted messages at optimal times. The plan includes a mix of short video content, in-app notifications and community-driven campaigns designed to enhance user acquisition, engagement, and retention, while ensuring alignment with the broader strategic goals of Taransit.